STUDY BAKING QUALITY OF SOME BREAD WHEAT GENOTYPES UNDER WATER STRESS - L. A. Hussain; M. S. Hamdalla; S. A. Yousif (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2023)
This study was aimed to investigate baking quality of some bread wheat and water stress. A field experiment was carried out at the fields of the College of Agricultural Engineering Sciences - University of Baghdad during the seasons 2018-2019 and 2019-2020. Five local cultivars and 20 entrance genotypes were planted, during first season and the best 9 genotypes for baking ability were selected and tested in the second season, under moisture depletion levels of 50, 70, and 90% of field capacity, RCBD was used for the first season, with a split-plot design for the second season, with three replications for both seasons. The levels of moisture depletion occupied the main plots and the genotypes of the sub plots. In the second season, the results showed that reducing the moisture depletion to the level of 50% of the available water produced the highest grain yield, while the 90% moisture depletion level exceeded 90% produced the highest means of the protein%. It could be concluded that the availability of the appropriate quantities of irrigation water reflected positively on grain yield and that the decrease in the quantities of irrigation water improved protein%.